Forest cover change in Peninsular Malaysia Using satellite remote sensing data [electronic resource] - 640157 Nazarin Ezzaty Mohd. Najib, 1991- , author; Kasturi Devi Kanniah, supervisor 603469; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2015